Improving the care of Lassa fever patients: re-evaluating the use of Ribavirin and characterising cardiovascular function - Salam, A (2024)

(untitled)
Lassa fever is a viral haemorrhagic fever, endemic to several West African countries. Case fatality rates average 30% across the literature. Ribavirin, a broad-spectrum antiviral agent, has been used to treat Lassa fever for four decades. Ribavirin is a pro-drug, metabolised to its active molecules intracellularly. Ribavirin has multiple different mechanisms of action. Ribavirin also has immunomodulatory effects. These antiviral and immunomodulatory effects appear to be cell- and dose- dependent. Ribavirin has toxicity at higher doses, notably haemolytic anaemia.